Analysis of benzimidazole anthelmintic resistance in parasitic nematodes Haemonchus contortus using nested isothermal amplification (PCR) - I. A. Pimenov; A. I. Varlamova; A. D. Afanasyev; I. M. Odoevskaya (Российский паразитологический журнал, 2024)
The purpose of the research is to monitor farms located in the European part of the Russian Federation to identify resistance to effects of benzimidazole anthelmintics in populations of nematodes Haemonchus contortus dwelling in the gastrointestinal tract of small cattle.Materials and methods. The studies were conducted in slaughterhouses located in the Moscow Region in 2023–2024. At the first stage, taxonomic identification of parasitic nematodes and larvae (L3) was made, and Strongylata species was determined from sheep. The study material was the abomasum with duodenum fragments and a distal rectum fragment with feces. For molecular studies, we used mature nematodes and H. contortus L3 larvae isolated from the abomasum and feces of small cattle brought to slaughterhouses in the Moscow Region from 8 regions of the European part of the Russian Federation: Moscow, Astrakhan, Oryol, Lipetsk, Tula, Bryansk regions, Stavropol and Dagestan. The studies were conducted at the premises of the Laboratory of Molecular Biology, the VNIIP – FSC VIEV. Statistical processing of the obtained data was made, and mean infection rates of parasitic nematodes (infection intensity and prevalence) were determined. Fifty-six DNA samples of nematodes H. contortus were examined using nested isothermal amplification (PCR) to identify gene alleles that determine resistance to benzimidazole drugs.Results and discussion. Molecular genetic studies of H. contortus DNA sampled from sheep brought from different Regions only detected homozygous individuals (100%) resistant to benzimidazole in the parasitic nematode population from the Oryol Region. Other regions identified only homozygous and heterozygous individuals susceptible to benzimidazole.